Community Views on Regional Government Policy in Handling Illegal Gold Mining in Merangin Regency - Abdhol Zikri; Michael Lega; Mirza Sazeta; M. Yusuf (Magister Ilmu Pemerintahan FISIP Universitas Mulawaraman, 2026)
This study aims to analyze public perceptions of local government policies in addressing Illegal Gold Mining (PETI) activities in Merangin Regency. This issue is crucial because it not only causes environmental degradation but also social risks and the community's economic dependence on illegal mining activities. Although various regulations have been implemented, previous studies have focused more on legal and environmental aspects, so there is still a gap in understanding the role of public perceptions on policy effectiveness. This study uses a quantitative approach with a survey method of 100 respondents in 12 affected sub districts. Data were analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM) through evaluation of the outer model (validity and reliability) and the inner model (relationships between variables). The variables analyzed include socialization, law enforcement, and environmental rehabilitation. The results show that all independent variables have a positive and significant effect on public views, with path coefficients of 0.353; 0.386; and 0.392, respectively (p < 0.05). Descriptively, public perception is in the positive category. However, a dilemma emerged between perception and behavior, where positive views were not followed by behavioral changes due to economic dependence on illegal mining. This research highlights the gap between policy acceptance and effectiveness. Therefore, integration of environmental rehabilitation and sustainable livelihood programs is needed to more effectively encourage community behavior change. In addition, further research is recommended to develop a mixed methods approach, expand the sample size, and test mediating variables such as economic factors and trust in government.